2005
DOI: 10.1111/j.1365-246x.2005.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Analogue modelling of the initiation of subduction

Abstract: S U M M A R YWe report the results of experiments on the initiation of subduction, using stratified analogue models in a large centrifuge, where the experiments are driven only by the enhanced gravity of the centrifuge without the effect of external lateral stresses. The scaled density of the stratified components resembles that of the asthenosphere and the continental and oceanic lithospheres. The experiments demonstrate that under the effect of enhanced gravity, the layers simulating the oceanic lithosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 42 publications
(71 reference statements)
2
41
0
1
Order By: Relevance
“…Some analogue models (e.g. Mart et al 2005) do resemble aspects of the examples described here; experiments by Lévy & Jaupart (2012) are closest to what is observed in eastern Indonesia, where subduction began during crustal extension at a continental margin.…”
Section: Discussionsupporting
confidence: 69%
“…Some analogue models (e.g. Mart et al 2005) do resemble aspects of the examples described here; experiments by Lévy & Jaupart (2012) are closest to what is observed in eastern Indonesia, where subduction began during crustal extension at a continental margin.…”
Section: Discussionsupporting
confidence: 69%
“…at the foot of the margin (e.g. Mart et al, 2005). The use of deep seismic tools for fault geometry at depth and the mapping and dating of turbidites in the deepest part of the basin may help in the future to further mitigate the seismic hazards of this fault system and to clarify the mechanisms of subduction inception.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Addition of water into the lithosphere ; Van der Lee et al, 2008). (9) Spontaneous thrusting of the buoyant continental/arc crust over the oceanic plate (Mart et al, 2005;Goren et al, 2008;Nikolaeva et al, 2010Nikolaeva et al, , 2011. (10) Small-scale convection in the sub-lithospheric mantle (Solomatov, 2004).…”
Section: Subduction Initiationmentioning
confidence: 99%
“…3b, 1.9-3.2 Myr). This type of subduction nucleation has been systematically modeled with both analogue (Mart et al, 2005;Goren et al, 2008) and 2D numerical (Nikolaeva et al, 2010(Nikolaeva et al, , 2011 techniques. With 2D models Nikolaeva et al (2010) investigated the factors controlling passive margins' stability and showed that three subsequent tectonic regimes can develop at a passive margin: (1) stable margin, (2) overthrusting, and (3) subduction.…”
Section: Subduction Initiationmentioning
confidence: 99%